Efficacy of non -thermal pressure plasma versus other modalities for disinfection of primary root canals - Shaymaa A. El Shishiny; Yomna O. Morad; Rania I. Hindi; Amina M. El-Motasem; Asmaa A. El Sheshiny; Dalia M. Alramady; Amira M. Samy (BMC Oral Health)
Abstract Background Endodontic treatment aims in the preservation of extremely carious primary teeth. For root canal therapy to be successful, root canals must be properly prepared and effectively irrigated .Therefore, it is necessary to select the proper root canal disinfection method to preserve the primary tooth. Objective This research was carried out to compare non-thermal pressure plasma (NTPP), diode laser, propolis, and chlorhexidine (CHX) efficacy for disinfection of deciduous anterior root canals contaminated with Enterococcus Faecalis (E. faecalis) after sterilization by gamma radiation. Methods In this study, forty extracted single-rooted primary anterior teeth were used. All teeth were cleaned, disinfected, and stored till use. Gaining access was provided till reaching the orifices of canals, all pulp tissue debris was removed, and root canals of all teeth were prepared. Standardized 8 mm root length was obtained through crown decronation below the cemento-enamel junction. Samples were sterilized by gamma radiation then the bacterial suspension was inoculated inside root canals. Specimens divided into four main groups; ten samples each group. Group I: Samples irrigated with chlorhexidine. Group II: Samples treated with diode laser. Group III: Samples irrigated with Ethanolic extract of propolis. Group IV: Samples treated with NTPP. Results A significant difference was found between values measured before and after four irrigation types (p < 0.001) for CHX, Diode Laser, NTPP and (P = 0.035) for Propolis. The highest values of colony reduction measured before and after irrigation were for NTPP (4.06 ± 0.88). Maximum reduction in colony-forming units was recorded in the NTPP group (98.79%), while the lowest reduction in colony-forming units was recorded in Propolis group (81.99%). Conclusion All tested methods (CHX, NTPP, Diode laser and Propolis) decreased colony count, with the highest reduction noted in group treated by NTPP and the least reduction noticed in Propolis treated group.